Hemisveric sebagai Sumber Ide Penciptaan Busana Pesta - Ani Robiha; Urip Wahyuningsih (BAJU: Journal of Fashion and Textile Design Unesa, 2023)
The hemisveric building has a unique beauty, this unique beauty makes this building a tourist spot. The purpose of this research is to describe the process of making and finished dresses with the source of the idea, namely the hemisveric, with the tucking technique. This research method uses a three stages design process approach or three stages of the design process. This method consists of 3 stages of research: problem definition and research, creative exploration and implementation. In the early stages of determining the design direction, namely making women's dresses with hemisveric sources of inspiration made for young women with the art of beat type. In the second stage, the researcher made a moodboard and developed 10 sketch designs for dresses in the form of one piece dresses. The two selected designs were created using construction and draping patterns. The implementation phase is implementing Cross Stitched Tucks and Slashed Trucks as the center of interest in party attire. The process of making tucking starts from preparing the bridal satin fabric that has been made in the form of tucking, then it is cut according to the design. The result of the party dress is as expected, namely a dress that fits the body properly for an art of beat type woman and applies a tucking decoration that applies the center of interest design principle.